VALIDATION METHODS FOR QUANTITATIVE DETERMINATION OF 4,4'-DIMETHYL-7,7'-ETHYLENDIOXY-2H-1-DIBENZOPYRAN-2,2'-DIONE SUBSTANCE - C. B. Nguyen; A. Z. Abyshev (Разработка и регистрация лекарственных средств, 2019)
Introduction. One of the most promising synthetic compounds of coumarin derivatives is immunacor-4,4'-dimethyl-7,7'-ethylenedioxy-2H-1-dibenzopyran-2,2'-dione. As a result of preclinical studies, it has been shown that it is promising in medical practice as an immunomodulator for the treatment and prevention of secondary immunodeficiency diseases.Aim. The objective of this work is to develop methods for HPLC and UV spectrophotometry to determine the quantitative determination of the immunacor substance and to study the complex of validation characteristics of the developed methods.Materials and methods. Quantitative analysis of the substance was carried out by UV-Spectrophotometry and HPLC. Validation procedures were performed on parameters: specificity, linearity, accuracy and precision in accordance with the requirements of FP XIV. Results and discussion. Validation characteristics have been determined, and their compliance with the relevant eligibility criteria has been experimentally verified.Conclusion. Methods for quantitative determination of the active component in 4,4'-dimethyl-7,7'-ethylenedioxy-2H-1-dibenzopyran-2,2'-dione (immunacor) pharmaceutical substance by HPLC and UV spectrophotometry has been developed. It is established that methods are specific, accurate, precise and linear in the analytical field. The precision HPLC method far exceeds the UV-spectrophotometry.